Perancangan penambahan fitur streaming channel televisi ekonomi pada SLiMS - Asykur Ahmad; Syarifah Rahmah; Agung Fatwanto (Nur Science Institute, 2026)
The development of information technology has encouraged libraries to improve digital services in order to provide faster and more relevant access to information. However, the digital library system at the Bank Indonesia Library has not integrated live financial news streaming services to support users’ real-time information needs. This study aims to design live streaming features for CNBC Indonesia, IDX Channel, and Bloomberg within the SLiMS-based digital library system. The study employed the Object-Oriented Analysis and Design method using the Unified Modeling Language approach to analyze system requirements and produce a streaming feature design. Data analysis was conducted through the identification of user needs, system architecture analysis, and evaluation of feature compatibility with the existing platform. The results showed that the streaming feature could be integrated into the SLiMS system to facilitate access to real-time financial news and information. The study concluded that the integration of streaming services has the potential to improve information accessibility and strengthen the role of digital libraries as providers of up-to-date financial information. Future research is recommended to focus on implementation testing and user experience evaluation.